Legitimacy of Income Generation Using Advertising Websites - Hamed Mirzakhan (مطالعات تطبیقی فقه و اصول مذاهب)
The present research is about the legitimacy of income generation using advertising websites and its typology. It is to say that today certain new transactions and contracts have emerged whose rulings are not different from those of the transactions that were common during the time of the Legislator or transactions that became customary a little after the time of the Legislator or from the transactions that are done every day in the markets of merchandise and services. The key question is what the ruling on acquiring money in this way is. Therefore, first of all the typology and then explaining the ruling for earning money through advertising websites is the main issue of this research, which is done by analytical-descriptive and discretionary (ijtahādī) procedure. By re-examining the jurisprudential arguments, jurisprudential evidences and rules explaining the evidences of acquiring money through Islamic contracts on the issue and criticizing and discretionary analysis of the evidences, it is possible to determine the acquisition of money through advertising websites. After critically reviewing the evidences of the permissibility of acquisition through ju‘āla (contract whose subject matter is a work or task to be done), bay‘ (sale), and ijāra (lease) contracts, eventually this type of acquisition of wealth is proved through the ju‘āla contract is proved. In addition, according to the jurisprudential rules of akl-i māl bi’l bāṭil (consuming property wrongfully) and ḍarar wa gharar (loss and risk-taking), the acquisition of wealth through non-conventional means and unreal visitation (through usury) is legally forbidden (ḥarām).